Research on AE and EMR response law of the driving face passing through the fault. (August 2019) - Qiu, Liming; Song, Dazhao; Li, Zhonghui; Liu, Baobei; Liu, Jie
Highlights: Revelation of the main unsafe factors of working face crossing the fault. The response characteristics of AE and EMR to the driving face crossing a fault. The method of detecting and real-time monitoring the fault by AE and EMR. Abstract: In this paper, the response characteristics of acoustic emission (AE) and electromagnetic radiation (EMR) to the driving face crossing a fault are analysed and tested. The method of real-time monitoring of the fault in front of the driving face by AE and EMR form coal is put forward. The results are as follows: (1) When passing through the fault, the large increase of stress in mining and fault superimposed stress, which makes it more likely to accumulate and release energy in the coal seam, is the main reason for the high risk of coal and gas outburst. (2) During crossing the fault, AE and EMR signals vary in stages, both the intensity and amplitude of the main frequency points of AE and EMR increase first and then decrease. (3) When the driving face is close to the fault, the main frequency of AE and EMR signals decreases and the frequency band concentrates. The main frequency ranges of AE and EMR signals are 3.66–22.5 kHz and 0.3–17.3 kHz, respectively. (4) The amplitudes of the main frequency points of the AE and EMR signals to the fault response. The change of the main frequency amplitude of AE and EMR signals can be used as the response index of the fault, and the response range is about 10 m. The research provides an effective monitoring method for structures in coal seam, which is of great significance to the safety production and rapid excavation of coal mines.